Opportunity-to-learn performance levels and student achievement gains for students with and without disabilities. (August 2020) - Kurz, Alexander; Reichenberg, Ray E.; Elliott, Stephen N.; Yel, Nedim
Abstract: This study examined within-year mathematics gains in the context of students' education status and teachers' opportunity-to-learn (OTL) performance for 60 general education teachers and 219 students with and without disabilities. Multilevel analyses did not support teachers' OTL performance as a statistically significant predictor of model slope or intercept. Effect sizes for the Level-2 intercept variance suggested that OTL performance has some utility in explaining variations in mean initial achievement level between teachers. Contingency tables for a subsample of teachers indicated that higher OTL performance resulted in greater achievement gain irrespective of education status with greater gain for students with disabilities. Highlights: OTL performance was not a statistically significant predictor of students' math gains. Predicted math gains increased with each higher level of teachers' OTL performance. Subsample analyses based on logging accuracy produced different results. Logging accuracy must be more carefully analyzed in future OTL studies.